Level of knowledge and hydration strategies of young soccer players - Fabrícia Geralda Ferreira; Janaína Lubiana Altoé; Rafael Pires Silva; Lilyane Perny Tsai; Alex de Alexandre Fernandes; Ciro José Brito; João Carlos Bouzas (Universidade Federal de Santa Catarina, 2009)
The aim of this study was to investigate fluid replacement strategies of young soccer players and their level of knowledge regarding hydration management. A total of 216 males (age: 18 ± 0.9 years) playing soccer for 8.7 ± 2.6 years were studied. The participants were members of four elite and subelite Brazilian soccer clubs. An exploratory descriptive study was conducted using a self-administered questionnaire consisting of 18 objective questions. The main results indicated that 32.3% and 30.1% of the athletes do not have an appropriate strategy for fluid replacement during competitions and training, respectively. In addition, 1.4% and 4.6% of the subjects reported to ingest no fluids during these exercise conditions. When asked about the type of solution (water or isotonic solution) consumed before, during and after exercise, water was the main fluid ingested during these periods. Approximately 80 athletes only ingest fluids when feeling thirsty. Coca-Cola® accounted for 11.1% of ingested fluids. Only 27.8% of the participants measure their body weight and 54.2% were unaware of the adequate strategy for fluid replacement. The most common symptoms reported by the athletes were cramps (53.2%), intense thirst (37.5%), and headache (33.8%). These results suggest that young soccer players have inappropriate fluid replacement habits, a fact that may lead to low performance during training or competition.